Imidazolized Activated Carbon Anchoring Phosphotungstic Acid as a Recyclable Catalyst for Oxidation of Alcohols With Aqueous Hydrogen Peroxide - Zheng, Min; He, Huiting; Li, Xiangzhou; Yin, Dulin (Frontiers in Chemistry, 2022)
Keggin-type phosphotungstic acid (HPW) supported on imidazolyl activated carbon (AC-COIMI-HPW) catalysts were prepared, which were used to catalyze the oxidation of benzyl alcohol with aqueous H2O2. In the presence of AC-COIMI-HPW, the benzyl alcohol conversion of 90.2% with 91.8% selectivity of benzaldehyde was obtained at 90°C for 6 h in acetonitrile aqueous solution. The catalyst exhibited an outstanding performance for the oxidation of various benzyl alcohols and aliphatic alcohols. In addition, the catalyst could be easily recovered and reused five times without significant deactivation. The characterization results showed that HPW was chemically bonded on the surface of the carbon materials through ionic bond. It is proposed that the combination of imidazole cation with HPW anion could not only tune the redox catalytic properties of the PW anion, but also enhance the compatibility of the catalyst in the reaction medium, thereby improving the catalytic performance.